5. Hematological Changes in Rattus Norvegicus infected with Trypanosoma evansi after Administration of Ethanol Extract of Phyllanthus Emblica - Dina Maulidya Siregar; Nuzul Asmilia; Yudha Fahrimal; Abdullah Hamzah; M. Hasan; Razali Daud; M. Isa; Dasrul Dasrul; Cut Nila Thasmi; Priyo Sambodo (Jurnal Medika Veterinaria, 2021)
This research aims to determine the value of erythrocyte, hemoglobin, and hematocrit of white rats (Rattus norvegicus) infected with Trypanosoma evansi and given ethanol extract of Malacca leaves (Phyllanthus emblica). The animals used in this study were 20 male rats. All rats were randomly divided into 5 treatment groups, each group consisting of 4 rats. The negative control group (K0) without T. evansi infection and without malacca leaf ethanol extract, the positive control group (K1) was infected with T. evansi without giving malacca leaf ethanol extract, the treatment group K2, K3, K4 were infected with T.evansi and were given ethanol extract Malacca leaf with doses of 300mg/kg BW, 600mg/kg BW, and 900mg/kg BW, respectively. The extract was given orally for 3 consecutive days. On the fourth day, blood was drawn for all groups through the orbital vein with a hematocrit pipette after administration of 0,2 ml Ketamin. Then the erythrocyte, hemoglobin, and hematocrit values were calculated using a hematology analyzer. The mean (± SD) erythrocyte values (106 / µl) were 7.66 ± 0.10, respectively; 2.65 ± 0.24; 4.56 ± 0.91; 6.58 ± 0.10; 5.86 ± 0.27; hemoglobin (g / dl) were 13.64 ± 0.26, respectively; 4.67 ± 0.13; 8.38 ± 0.72; 11.25 ± 0.58; 9.55 ± 0.56, the hematocrit (%) were 40.97 ± 0.67, respectively; 28.27 ± 0.76; 30.44 ± 0.48; 37.70 ± 0.40; 34.06 ± 0.17. The results showed that administration of ethanol extract of malacca leaves at a dose of 600mg/kg BB had a significant effect in maintaining the value of erythrocytes, hemoglobin, and hematocrit of white rats that had been infected with Trypanosoma evansi.